2019
DOI: 10.26891/jik.v13i2.2019.55-62
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Protozoa Usus Oportunistik dan Faktor Risikonya Pada Anak Panti Asuhan Kota Pekanbaru

Abstract: Opportunistic intestinal protozoa are protozoa that can infect humans at a time when the body’s defense system isdeclining (immunocompromising). Opportunistic protozoan infections are infections by intestinal protozoa that werenot previously considered important, but now can cause disease in humans. Opportunistic intestinal protozoan infectionsbesides being found in immunocompromised patients are also reported to infect children. Some of the intestinalprotozoan species that have been identified to cause infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
5
1
1
1
Order By: Relevance
“…infection. This is in line with study by (Maryanti et al, 2019) that reported there was no significant difference between the hygiene behavior and Giardia spp. infection.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…infection. This is in line with study by (Maryanti et al, 2019) that reported there was no significant difference between the hygiene behavior and Giardia spp. infection.…”
Section: Discussionsupporting
confidence: 92%
“…infection. This finding is in line with the research that conducted by (Maryanti et al, 2019) The study revealed that there was no significant relationship between latrine habits and Giardia spp. infection.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The result of the microscopic examination of stool samples showed that 29 (41.4%) of the children's stools were found positive for opportunistic intestinal protozoans (Table 2). The results of this study revealed a higher prevalence of opportunistic intestinal protozoans compared to a previous study conducted 4 years ago which found that 11 (24.6%) orphanage children in Pekanbaru were positive opportunistic intestinal protozoa (Maryanti et al, 2019). The result indicated that good practice of personal hygiene and sanitation in the children's environment is still an issue.…”
Section: Resultscontrasting
confidence: 48%